Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) Communities and the Coronavirus Disease 2019 Pandemic: A Call to Break the Cycle of Structural Barriers. (29th July 2021) - Gil, Raul Macias; Freeman, Tracey L; Mathew, Trini; Kullar, Ravina; Fekete, Thomas; Ovalle, Anais; Nguyen, Don; Kottkamp, Angélica; Poon, Jin; Marcelin, Jasmine R; Swartz, Talia H
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately impacted lesbian, gay, bisexual, transgender, and queer (LGBTQ+) communities. Many disparities mirror those of the human immunodeficiency virus (HIV)/AIDS epidemic. These health inequities have repeated throughout history due to the structural oppression of LGBTQ+ people. We aim to demonstrate that the familiar patterns of LGBTQ+ health disparities reflect a perpetuating, deeply rooted cycle of injustice imposed on LGBTQ+ people. Here, we contextualize COVID-19 inequities through the history of the HIV/AIDS crisis, describe manifestations of LGBTQ+ structural oppression exacerbated by the pandemic, and provide recommendations for medical professionals and institutions seeking to reduce health inequities. Abstract : This perspective describes the impact that COVID-19 has had on lesbian, gay, bisexual, transgender, and queer communities and how the history of this group's advocacy from the HIV/AIDS epidemic can inform the care of this highly minoritized population.